The frequency of Anti-hepatitis B core antibody in Negative Hepatitis B surface Antigen Blood Donors in Thi-Qar province - Alyaa A. Hafedh; Saad, A. Ateia; Hind M. Musa (University of Thi-Qar Journal, 2019)
Viral Hepatitis Type B is an important public health problem throughout the world. Hepatitis B virus still a major causes of chronic hepatitis. Although, the blood banks using HBsAg as a screening test for HBV , the post transfusion infections remain occur . the aim of this study is the assessment of efficacy of anti-HBc detection test in screening for HBV infections among the blood donors who were negative for HBs Ag in Thi-Qar province . A total of 352 blood donors negative for HBsAg divided into 236 (urban) and 116 persons (rural) were involving in the study and anti-HBc antibody was detected by using ELISA technique . The study shown that the frequency of anti-HBcwas high among blood donors was 16 ( 4.54%) , with no significant differences between urban 8 (6.89%) and rural 8 (3.34%) groups under ( p< 0.05 ) . The frequency of anti-HBc among blood donors was high and there was no relationship between this marker and resides of donors